Reconstruction of chronic extensor hallucis longus tendon rupture using plantaris tendon graft - Villar, Ricardo Ummen de Almeida Tenório; Benevides , Pedro Costa; Nery, Caio Augusto de Souza; Prado , Marcelo Pires; Alloza , José Felipe Marion; Masagão , Renato do Amaral; Godoy-Santos , Alexandre Leme (Journal of the Foot & Ankle, 2021)
Chronic tendon ruptures can be difficult to manage as end-to-end repair can be challenging. In this scenario, reconstruction techniques with tendon grafts may be useful. The ideal tendon graft would be one that has similar biomechanical properties, low donor-site morbidity and length compatible with the tendon gap. We describe a safe technique for the reconstruction of a chronic extensor hallucis longus tendon rupture using a plantaris tendon graft. Level of Evidence V, Therapeutic Studies; Expert Opinion.